2020
DOI: 10.3390/s20195709
|View full text |Cite
|
Sign up to set email alerts
|

Force Shadows: An Online Method to Estimate and Distribute Vertical Ground Reaction Forces from Kinematic Data

Abstract: Kinetic models of human motion rely on boundary conditions which are defined by the interaction of the body with its environment. In the simplest case, this interaction is limited to the foot contact with the ground and is given by the so called ground reaction force (GRF). A major challenge in the reconstruction of GRF from kinematic data is the double support phase, referring to the state with multiple ground contacts. In this case, the GRF prediction is not well defined. In this work we present an approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Similarly, some studies have confirmed that the RFD is indicated by the slope of the force-time curve. The lower limbs could exert a greater force in a shorter period of time, which also shows that the number of muscle fibers determines the amount of force generated [45][46][47]. Some studies have pointed out that an excellent vertical jump is dominated by the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have confirmed that the RFD is indicated by the slope of the force-time curve. The lower limbs could exert a greater force in a shorter period of time, which also shows that the number of muscle fibers determines the amount of force generated [45][46][47]. Some studies have pointed out that an excellent vertical jump is dominated by the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…In sports performance laboratories, the force plates are routinely used [526,759], but recently low-cost insoles [195,250,378,612,795,864] and Nintendo R Wii Balance Board TM [543] have been investigated as alternatives as the cost of force plates can be prohibitive in some cases. Recently, nonlearning mathematical [863], and deep learning models have been developed to approximate the forces generated by the athlete, solely from nonkinetic measurements, such as from kinematic data [323,375,724]. These approaches naturally require development datasets with the both modalities (kinematic and kinetic) in order to validate the approximation accuracy of the model when deploying to real-world use just with the kinematic modality.…”
Section: B Kinetic: Force Measurementmentioning
confidence: 99%